A machine tool motorized spindle with hybrid structure of steel and carbon fiber composite. Issue 1 (2019) - Kono, Daisuke; Mizuno, Soichiro; Muraki, Toshiyuki; Nakaminami, Masamitsu
Abstract: Carbon fiber reinforced plastic (CFRP) is a promising material for enhancing the spindle performance of machine tools because of its high specific stiffness and low thermal expansion. However, when a conventional steel spindle shaft is replaced by a CFRP shaft, the anisotropic property of CFRP makes it difficult to maintain the static stiffness that is equivalent to that of conventional spindles. This study proposes a hybrid structure of steel and CFRP to avoid reduced stiffness of the shaft. Fundamentals of shaft design are described to enable discussion of a favorable steel-CFRP ratio. An experimental evaluation of a developed CFRP spindle is also reported.